Effect of functional exercises on the explosive ability and accuracy of shooting from outside the three-point line in advanced basketball players - Mustafa A. Abood; Jamal S. Al Abdullah; Samer A. Al Midhatee (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.